(untitled) (Balneo and PRM Research Journal, 2024)
Primary osteoporosis, a geriatric bone metabolic condition affecting both the mineral density and the microarchitecture, comes with a complex burden. Bone turnover markers tidily reflect the changes of skeleton status that are part of the physiological process or theyhighlight the abnormal status including in osteoporosis in addition to other biomolecules evaluation such as hormones, inflammatory markers, myokines and adipokines. In this narrative review, we aimed to highlight several aspects regarding osteoporosis-related rehabilitation amid mitigating the role of physical exercise as bone formation booster. Bone turnover markers assays, by capturing the essence of the bone remodelling, registered a great progress during latest years, thus show-ing an enhanced index of applicability in daily practice (despite being known and studied for more than three decades). Irisin, a novel player in the muscle-bone-metabolism cross-talk, represents a muscle-derivate hormone that is expected to highlight the interplay between physical exercise and bone formation. Other concurrent signal transduction pathways include recently described biomarkers such as preptin or the spectrum associated with serotonin-LRP5-Wnt/beta catenin canonical and non-canonical loops. Current pitfalls of the topic include the personalized recommendation of physical activity due to severe co-morbidities, the lack of homogenous studies to measure the intervention and the consecutive bone health and great variations of using the bone turnover markers amid daily pracPrimary osteoporosis, a geriatric bone metabolic condition affecting both the mineral density and the microarchitecture, comes with a complex burden. Bone turnover markers tidily reflect the changes of skeleton status that are part of the physiological process or theyhighlight the abnormal status including in osteoporosis in addition to other biomolecules evaluation such as hormones, inflammatory markers, myokines and adipokines. In this narrative review, we aimed to highlight several aspects regarding osteoporosis-related rehabilitation amid mitigating the role of physical exercise as bone formation booster. Bone turnover markers assays, by capturing the essence of the bone remodelling, registered a great progress during latest years, thus show-ing an enhanced index of applicability in daily practice (despite being known and studied for more than three decades). Irisin, a novel player in the muscle-bone-metabolism cross-talk, represents a muscle-derivate hormone that is expected to highlight the interplay between physical exercise and bone formation. Other concurrent signal transduction pathways include recently described biomarkers such as preptin or the spectrum associated with serotonin-LRP5-Wnt/beta catenin canonical and non-canonical loops. Current pitfalls of the topic include the personalized recommendation of physical activity due to severe co-morbidities, the lack of homogenous studies to measure the intervention and the consecutive bone health and great variations of using the bone turnover markers amid daily practice in different centers. To conclude, part of the monitoring protocol in osteoporotic patients under specific medication against osteoporosis or during bisphosphonates drug holiday, bone turnover markers assays stands for a practical insight in every day practice. The contributing role of physical exercise to boost bone formation as reflected by these biomolecules is well understood across a multitude of signal transduction pathways. However, a current gap in practical use and surveillance of the prescription of physical activity, mechanical load and rehabilitation programs in these patients is confirmed so far.tice in different centers. To conclude, part of the monitoring protocol in osteoporotic patients under specific medication against osteoporosis or during bisphosphonates drug holiday, bone turnover markers assays stands for a practical insight in every day practice. The contributing role of physical exercise to boost bone formation as reflected by these biomolecules is well understood across a multitude of signal transduction pathways. However, a current gap in practical use and surveillance of the prescription of physical activity, mechanical load and rehabilitation programs in these patients is confirmed so far.